PD-L1 expression level in different thymoma stages and thymic carcinoma: a meta-analysis. Issue 4 (August 2020) - Chen, Hua-Fei; Wu, Li-Xin; Li, Xiao-Feng; Zhu, You-Cai; Pan, Wei-Wei; Wang, Wen-Xian; Xu, Chun-Wei; Huang, Jian-Hui; Wu, Min-Hua; Du, Kai-Qi
Background: The immune checkpoint ligand, programmed cell death 1 ligand 1 (PD-L1), is expressed in various tumors and associated with response to drugs that target programmed cell death protein 1. Previous studies have estimated the level of PD-L1 expression among different stages of thymoma and thymic carcinoma to evaluate its potential use as a diagnostic factor; however, its varying expression level has been problematic. We conducted this meta-analysis of published literature to evaluate PD-L1 expression in thymomas and thymic carcinomas. Methods: We analyzed 12 studies that included 320 patients with type A/AB/B1 thymoma, 225 patients with type B2/B3 thymoma, and 180 patients with thymic carcinoma. Results: No difference in PD-L1 expression level was found between the B2/B3 vs C groups (odds ratio [OR], 0.67; 95% confidence interval [CI], 0.26, 1.76; p = 0.42). However, the heterogeneity was very high ( I 2 = 78%), and a significant difference was found between groups A/AB/B1 and B2/B3 (OR, 0.22; 95% CI, 0.12, 0.41; p < 0.001), with a relatively low heterogeneity ( I 2 = 55%). Conclusion: PD-L1 positivity might be a useful factor to differentiate type A/AB/B1 thymoma from type B2/B3 and thymic carcinoma. This result might be valuable for potential anti PD-L1 treatment in thymoma and thymic carcinoma.